2022
DOI: 10.1038/s41598-022-13964-x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of adipose tissue revealing differentially abundant proteins in highly efficient mid-lactating dairy cows

Abstract: The improvement of nutrient utilization efficiency in dairy cows represents an important task in view of the current rising demand for animal products and sustainable resource usage. In this perspective, the identification of appropriate markers to identify the most efficient animals for dairy production becomes a crucial factor. Residual feed intake (RFI), which represents the difference between predicted and actual intake, is used to define the efficiency of cows. In this study, subcutaneous adipose tissue (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Adipose tissue, as the main energy reserve of mammals, plays a crucial role in milk production in dairy cows. Ben Meir et al (2022) found that transferrin is a differentially expressed protein in mid-lactation cows through proteomics, which is upregulated in eight Fe-related pathways and can be used as a candidate biomarker. Three SNPs of transferrin were detected in a recent study ( Ali et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Adipose tissue, as the main energy reserve of mammals, plays a crucial role in milk production in dairy cows. Ben Meir et al (2022) found that transferrin is a differentially expressed protein in mid-lactation cows through proteomics, which is upregulated in eight Fe-related pathways and can be used as a candidate biomarker. Three SNPs of transferrin were detected in a recent study ( Ali et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…These genes might affect the meat quality traits of Qaidam cattle by affecting adipocyte differentiation and adipogenesis. In terms of lactation function, there are differences in protein expression of RBM39 in inefficient and efficient lactating cows, which is proved to be related to lactation function (Ben Meir et al., 2022). TONSL is found to be related to milk production, which affects the percentage of fatty acids and milk fat and was selected in the genome‐wide association analysis of Chinese Holstein cattle and Canadian Holstein cattle (Ibeagha‐Awemu et al., 2016; Peters et al., 2021; Wang et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In llama, most of the selection signatures encompasses loci involved in the regulation of reproduction and maternal traits: some are involved in the lipid metabolism during lactation, as ARFGEF2 and FZD9 which are known for their role in fatty acid transport [ 36 ] adipocytes differentiation [ 37 ] and quantity of milk produced [ 38 ]. Similarly, the PHF20 gene is involved in milk production [ 39 ] and lactating efficiency [ 40 ], while RCOR1 is a candidate gene implicated in lactose synthesis and milk yield [ 41 ]. Moreover, signatures of selections in llama suggested selection for efficient reproductive performances in harsh environments.…”
Section: Discussionmentioning
confidence: 99%